5- or/and 20-O-alkyl-2, 3-dehydrosilybins: Synthesis and biological profiles on prostate cancer cell models. Issue 17 (1st September 2017) - Vue, Bao; Zhang, Xiaojie; Lee, Timmy; Nair, Nandini; Zhang, Sheng; Chen, Guanglin; Zhang, Qiang; Zheng, Shilong; Wang, Guangdi; Chen, Qiao-Hong
Graphical abstract: Abstract: To investigate the effects of alkylation at 5-OH and 20-OH of 2, 3-dehydrosilybin on prostate cancer cell proliferation, the synthetic approaches to 5- or/and 20- O -alkyl-2, 3-dehydrosilybins, through a multi-step sequence from commercially available silybin, have been successfully developed. The first three reactions in the syntheses were completed through a one-pot procedure by managing anaerobic and aerobic conditions. With these synthetic methods in hand, twenty-one 2, 3-dehydrosilybins, including seven 20- O -alkyl, seven 5, 20- O -dialkyl, and seven 5- O -alkyl-2, 3-dehydrosilybins, have been achieved for the evaluation of their biological profiles. Our WST-1 cell proliferation assay data indicate that nineteen out of the twenty-one 2, 3-dehydrosilybins possess significantly improved antiproliferative potency as compared with silybin toward both androgen-sensitive (LNCaP) and androgen-insensitive prostate cancer cell lines (PC-3 and DU145). 5- O -Alkyl-2, 3-dehydrosilybins were identified as the optimal subgroup that can consistently inhibit cell proliferation in three prostate cancer cell models with all IC50 values lower than 8 µM. Our flow cytometry-based assays also demonstrate that 5- O -heptyl-2, 3-dehydrosilybin effectively arrests the cell cycle in the G0 /G1 phase and activates PC-3 cell apoptosis.